Analysis of the cost of international education in selected countries / Ershad Ali , Geetha Subramaniam - Ali, Ershad; Subramaniam, Geetha (Faculty of Business Management, 2010)
© University Publication Centre (UPENA) and Institute of Business Excellence 2180-2777 50 ANALYSIS OF THE COST OF INTERNATIONAL EDUCATION IN SELECTED COUNTRIES Ershad Ali Auckland Institute of Studies, New Zealand Geetha Subramaniam Universiti Teknologi MARA and Victoria University of Wellington, New Zealand Abstract This paper examines the cost of education for international students in selected countries: New Zealand, Australia, USA, UK, Canada and Ireland. These countries export education since long and each one is a competitor for another one. The study defines the cost of education as the total cost that a student has to bear for obtaining a degree. Total cost includes annual tuition fee, living cost, and other costs such as insurance premium. The study collected data from official data sources of the respective countries. The study compared costs and found that cost of education is varied for a specific program from one country to another. It is also varied from one university to another within a country. However, the most costly education is in USA while the cheapest one is in New Zealand. The findings of this study might be useful for researchers, policy makers and educationists.